2016
DOI: 10.1155/2016/3164105
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Use among Patients with Psoriasis in Taiwan: A Nationwide Population‐Based Study

Abstract: Traditional Chinese medicine (TCM) has long been used for patients with psoriasis. This study aimed to investigate TCM usage in patients with psoriasis. We analyzed a cohort of one million individuals representing the 23 million enrollees randomly selected from the National Health Insurance Research Database in Taiwan. We identified 28,510 patients newly diagnosed with psoriasis between 2000 and 2010. Among them, 20,084 (70.4%) patients were TCM users. Patients who were female, younger, white-collar workers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…43 For example, our previous studies revealed that 63.11% of children with allergic rhinitis and 57.95% of children with asthma used TCM, 44 higher than the overall average use of TCM by children (22.5%). 23 Our recent study also found that 70.4% of patients with psoriasis used TCM, 45 much higher than the overall percentage of TCM users in Taiwan (28.66%). 33 We propose 2 possible explanations for the low use of TCM in our population.…”
Section: Discussionmentioning
confidence: 82%
“…43 For example, our previous studies revealed that 63.11% of children with allergic rhinitis and 57.95% of children with asthma used TCM, 44 higher than the overall average use of TCM by children (22.5%). 23 Our recent study also found that 70.4% of patients with psoriasis used TCM, 45 much higher than the overall percentage of TCM users in Taiwan (28.66%). 33 We propose 2 possible explanations for the low use of TCM in our population.…”
Section: Discussionmentioning
confidence: 82%
“…Traditional Chinese medicine (TCM) therapy used in Taiwan has been enrolled in the National Health Insurance Research Database since 2002 [ 1 , 2 ]. Herbal formulas and single herbs, such as Fang-Feng ( Saposhnikovia divaricate ) and Bai-Xian-Pi ( Dictamni dasycarpus ; D. dasycarpus ), were prescribed for treating dermatitis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is an inflammatory skin disease characterized by a significant elevation in the concentration of cytokines, including TNF-α ( 26 , 27 ). The annual cost of psoriasis in China alone is estimated to be over <1 billions of yuan, and the socioeconomic burden of psoriasis has an important influence on the Chinese healthcare system ( 28 ). However, because the underlying mechanism remains undetermined, current treatments have not yet fully met the needs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…TCM has been developed and applied by the Chinese over a long period of time, and includes acupuncture, Chinese traumatology and CHM; CHM is considered to be the most popular type of TCM worldwide ( 33 , 34 ). It has been reported that various CHM formulations have been used for the treatment of a number of diseases, including gastrointestinal disease, diabetes mellitus and psoriasis ( 28 , 35 , 36 ). In China, numerous patients with psoriasis accept treatment with CHM, and ~2% of patients receive similar therapy in the USA ( 37 ).…”
Section: Discussionmentioning
confidence: 99%